Complete plastid genome sequence of Halimodendron halodendron (Leguminosae). Issue 8 (3rd August 2021) - Yan, Wen-Jie; Yang, Tian-Ge; Qin, Er-Dai; Qu, Wen-Rui; Wu, Zhi-Hua; Jiao, Pei-Pei; Liu, Hong
Abstract: Halimodendron halodendron (Pall.) Voss. is a deciduous shrub belonging to the genus Halimodendron, Leguminosae, and is mainly distributed in dry areas. This species can be used for saline-alkali soil improvement and sand fixation. The complete plastid genome of H. halodendron first reported here is 129, 342 bp in length, and contains 110 genes, including 76 protein coding genes, 30 tRNA genes, and 4 rRNA genes. A total of 105 simple sequence repeats (SSRs) were identified in the chloroplast genome. This information will be useful for study on the evolution and genetic diversity of Halimodendron halodendron in the future.